2017
DOI: 10.1159/000484441
|View full text |Cite
|
Sign up to set email alerts
|

Association of Haemodynamic Indices of Central and Peripheral Pressure with Subclinical Target Organ Damage

Abstract: Background: Central aortic pressure has often been shown to be more closely associated with markers of vascular function and incidence of cardiovascular events compared to peripheral pressure. However, the potential clinical use of central aortic or peripheral haemodynamic indices as markers of target organ damage (TOD) has not been fully established. Methods: We evaluated associations of TOD with central aortic and peripheral haemodynamic indices (central aortic [cPP] and peripheral pulse pressure [pPP], cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…As age was a main susceptibility factor of CIMT ( 30 ), we stratified age by 60 years and then we found that CIMT abnormality was significantly lower in Group ( CBP ) compared with Group ( control ). A previous study suggested that each SD increase in pPP and cPP was associated with an increased risk of carotid IMT >0.9 mm ( 31 ). Various studies have illustrated that cf-PWV was significantly related to CIMT and arterial plaque ( 3 , 32 ).…”
Section: Discussionmentioning
confidence: 98%
“…As age was a main susceptibility factor of CIMT ( 30 ), we stratified age by 60 years and then we found that CIMT abnormality was significantly lower in Group ( CBP ) compared with Group ( control ). A previous study suggested that each SD increase in pPP and cPP was associated with an increased risk of carotid IMT >0.9 mm ( 31 ). Various studies have illustrated that cf-PWV was significantly related to CIMT and arterial plaque ( 3 , 32 ).…”
Section: Discussionmentioning
confidence: 98%
“…Theoretically, aortic stiffness increases the effects of wave reflection of the pressure waveform, leading to various unfavorable hemodynamic consequences, such as increased left ventricular afterload, which can lead to damage of the heart muscle ( 17 ), and this is consistent with the relationship between cf-PWV and LVH. The lack of correlation between BP and heart damage may be related to the following factors: Our previous study ( 19 ) suggested that both peripheral pulse pressure (PPP) and central pulse pressure (CPP) were related to target organ damage in populations with hypertension. Compared with PPP, CPP has a higher predictive ability for target organ damage over 60 years old.…”
Section: Discussionmentioning
confidence: 99%